Foreignism and Gulliver's Complex: Brazilian people in the perception of expatriates from different origins - de Araújo, Bruno Felix Vonborell; Teixeira, Maria Luisa Mendes; Malini, Elise (Organizações & Sociedade, 2013)
The aim of this study was to understand, face to the Gulliver Complex approach,how self-initiated expatriates from different backgrounds perceive the relationshipbetween Brazilian people and foreigners. The study, that is exploratory and qualitative,was carried out through semi-structured interviews with 33 self-initiatedexpatriates, 17 from developed countries and 16 from developing countries. The resultssuggest that the foreignism can be understood as an aspect of Brazilian culture,bipolar, where one pole is related to the care of the Brazilian with the foreigner, andthe other represents the arrogant behavior torward the foreigner, showing a relationshipof compensation, as represented in the Gulliver Complex. The results suggestthat behaviors of superiority or inferioriry cannot be explained only by the foreignernationality, but by the origin suggested by the physical appearance of the foreigner.